Concentrate Supplementation in Fattening Ration of Young Goat in Wamena, Irian Jaya - Wartika Rosa Farida (Media Veteriner, 1998)
Twelve native young goats were used in this study to observe the effects of concentrate supplementation in ration such as sweet potatoes and rice brand on consumption, digestion, and growth development of young goats. The results showed that sweet potatoes and rice brand supplementation, respectively, 300 g and 30 g per head per day in goat's ration increased the consumption of dry matter, protein, fat, N-free extract, digestion of dry matter and N-balance. This ration also improved daily body weight gain and feed conversion.Key words: concentrate, fattening ration, growth, goats